Providing holistic care to children with cerebral palsy treated with transnasal neural stem cell transplantation - Li, Xiaoyan; Li, Mengyao; Qin, Xixian; Li, Ying; Wang, Yachen; Han, Chao; Ni, Shiwei; Sun, Xuna; Dong, Peipei; Liu, Jing (Frontiers in Pediatrics, 2024)
Objective: Holistic care is a key element in nursing care. Aiming at the heterogeneous disease of cerebral palsy, researchers focused on children with cerebral palsy who received transnasal transplantation of neural stem cells as a specific group. Based on establishing a multidisciplinary team, comprehensive care is carried out for this type of patient during the perioperative period to improve the effectiveness and safety of clinical research and increase the comfort of children.Between January 2018 and June 2023, 22 children with cerebral palsy underwent three transnasal transplants of neural stem cells.No adverse reactions related to immune rejection were observed in the 22 children during hospitalization and follow-up. All children tolerated the treatment well, and the treatment was superior. One child developed nausea and vomiting after sedation; three had a small amount of bleeding of nasal mucosa after transplantation. Two children had a low fever (≤38.5℃), and one had a change in the type and frequency of complex partial seizures. Moreover, 3 children experienced patch shedding within 4 hours of patch implantation into the nasal cavity.The project team adopted nasal stem cell transplantation technology. Based on the characteristics of transnasal transplantation of neural stem cells in the treatment of neurological diseases in children, a comprehensive and novel holistic care plan is proposed. It is of great significance to guide caregivers of children to complete proper care, further improve the safety and effectiveness of treatment, and reduce the occurrence of complications.